EFFECT OF TRAINING AND REWARD SYSTEM ON EMPLOYEE PERFORMANCE (STUDY AT PT. BIO FARMA PERSERO) - Ekabawani, Rianti; Winarno, Alex (Jurnal Ekonomi Balance, 2019)
This research aims to determine the effect of Training and Reward System on the performance of employees of PT. Bio Farma (Persero). This goal is motivated by the phenomenon of the problem being faced by the company PT. Bio Farma (Persero), which is the achievement of employee performance in 2016 to 2018, has not yet reached the expected target. Among the many factors that can affect employee performance, there are two main factors that will be reviewed in this study. The two factors are training and reward system. Taking these two factors is based on the results of interviews with the company and is supported by data that has been collected. This research uses quantitative methods with data analysis techniques used are descriptive analysis and regression. The number of samples in this study were 30 employees of PT. Bio Farma (Persero) Division of Human Resources is determined by the saturation sampling method. Based on the results of research that has been done it can be concluded that the training and reward system has a significant and positive effect on employee performance with a score of 76.4%. These results support the implementation of training and reward systems at PT. Bio Farma (Persero) so that it can have an impact on improving the performance of its employees.